2012
DOI: 10.1111/j.1360-0443.2012.04028.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention to health warnings on plain tobacco packaging in adolescent smokers and non‐smokers

Abstract: Among experimenters and weekly smokers, plain packaging increases visual attention to health warnings and away from branding. Daily smokers, even relatively early in their smoking careers, seem to avoid the health warnings on cigarette packs. Adolescent never-smokers attend the health warnings preferentially on both types of packs, a finding which may reflect their decision not to smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 13 publications
9
92
1
7
Order By: Relevance
“…It was concluded that adolescents who never smoked paid attention to health warnings in different types of packaging, a behaviour that may be related to their decision not to smoke. The behaviour of smokers was quite different (Maynard, Munafò, & Leonards, 2013). A better understanding of the visual attention of smokers and non-smokers can aid in the effectiveness of specific campaigns for these groups of adolescents.…”
Section: Social Marketingmentioning
confidence: 98%
“…It was concluded that adolescents who never smoked paid attention to health warnings in different types of packaging, a behaviour that may be related to their decision not to smoke. The behaviour of smokers was quite different (Maynard, Munafò, & Leonards, 2013). A better understanding of the visual attention of smokers and non-smokers can aid in the effectiveness of specific campaigns for these groups of adolescents.…”
Section: Social Marketingmentioning
confidence: 98%
“…Laboratory research also shows that, relative to branded packaging, plain cigarette packaging reduces motivation to purchase cigarettes (Brose et al 2014), self-reported engagement in smoking (Moodie et al 2011;Moodie and Mackintosh 2013), the likelihood of accepting a packet of cigarettes (Hammond, Daniel, and White 2013), and engagement in tobacco-seeking behavior . Alongside reducing the activation of learned habits, research suggests that plain cigarette packaging could also change consumer behavior by increasing consumers' attention and positive attitudes towards health warnings displayed on packs Maynard, Munafò, and Leonards 2013;Munafò et al 2011). …”
Section: Removing or Reducing Exposure To Situational Cues That Activmentioning
confidence: 99%
“…These countries should consider adopting plain packaging to strengthen the effectiveness of their PHWs, as recommended by the implementation guidelines of Articles 11 and 13 of the WHO FCTC 32 . There is evidence that PHWs are more salient when introduced on plain packaging [47][48][49][50] . Some studies have also related plain packaging with increased urgency among smokers to quit, and with increased quit attempts 51,52 .…”
Section: Tobacco Prevention and Cessationmentioning
confidence: 99%